Cathodic Electrodeposition and Characterization of ni3se2 thin Films - K Anuar; Z Zainal; N Saravanan; A.R Kartini (Universitas Gadjah Mada, 2004)
Nickel selenide thin films have been potentiostatically electrodeposited on titanium substrate at room temperature from aqueous solution containing Ni-EDTA and Na2SeO3. Various deposition potentials were attempted in order to determine the optimum electrodeposition potential. The films were characterised using x-ray diffraction analysis (XRD) and the photoactivity of the electrosynthesised films were studied using linear sweep voltammetry (LSV). The band-gap energy was determined using UV-visible spectroscopy. The XRD analysis indicated the formationof polycrystalline Ni3Se2. The film exhibited p-type semiconductor behaviour with good photosensitivity. The bandgap energy (Eg) was about 1.4eV.